The Bioequivalence of Tafamidis 61‐mg Free Acid Capsules and Tafamidis Meglumine 4 × 20‐mg Capsules in Healthy Volunteers. Issue 7 (20th March 2020) - Lockwood, Peter A.; Le, Vu H.; O'Gorman, Melissa T.; Patterson, Terrell A.; Sultan, Marla B.; Tankisheva, Ekaterina; Wang, Qiang; Riley, Steve
Abstract: Tafamidis, a non‐nonsteroidal anti‐inflammatory benzoxazole derivative, acts as a transthyretin (TTR) stabilizer to slow progression of TTR amyloidosis (ATTR). Tafamidis meglumine, available as 20‐mg capsules, is approved in more than 40 countries worldwide for the treatment of adults with early‐stage symptomatic ATTR polyneuropathy. This agent, administered as an 80‐mg, once‐daily dose (4 × 20‐mg capsules), is approved in the United States, Japan, Canada, and Brazil for the treatment of hereditary and wild‐type ATTR cardiomyopathy in adults. An alternative single solid oral dosage formulation (tafamidis 61‐mg free acid capsules) was developed and introduced for patient convenience (approved in the United States, United Arab Emirates, and European Union). In this single‐center, open‐label, randomized, 2‐period, 2‐sequence, crossover, multiple‐dose phase 1 study, the rate and extent of absorption were compared between tafamidis 61‐mg free acid capsules (test) and tafamidis meglumine 80‐mg (4 × 20‐mg) capsules (reference) after 7 days of repeated oral dosing under fasted conditions in 30 healthy volunteers. Ratios of adjusted geometric means (90%CI) for the test/reference formulations were 102.3 (98.0‐106.8) for area under the concentration‐time profile over the dosing interval and 94.1 (89.1‐99.4) for the maximum observed concentration, satisfying prespecified bioequivalence acceptance criteria (90%CI, 80‐125). Both tafamidis regimens had an acceptable safety/tolerability profile in this population.